Phase angle, impedance ratio, and athletic performance of young adult Japanese track and field throwers - Hikita, A.; Oshita, K.; Myotsuzono, R.; Murai, S. (Physiological Reports, 2026)
This study investigated the relationship between World Athletics (WA) points and body size, body composition, phase angle (PhA), and impedance ratio (IR) among young adult Japanese university track and field throwing athletes. Twenty-five female and 39 male athletes (11 and 14 javelin throwers, 5 and 13 discus throwers, 6 and 7 hammer throwers, 3 and 5 shot putters; and WA points: 852.5 ± 90.3 and 831.8 ± 105.4, respectively) underwent body composition, PhA, and IR measurements using bioelectrical impedance analysis, and their best competition records for the season were examined. No significant relationship was found between WA points and body size. While no significant relationship was found between WA points and fat-free mass in females, a weak relationship was observed in males. Therefore, the importance of muscle mass in throwing performance may differ across the four disciplines. However, PhA and IR were significantly and substantially related to WA points in both sexes. Furthermore, the higher WA points group had significantly higher PhA and lower IR values than the lower WA points group, with large effect sizes. These results suggest that PhA and IR, which are indicators of muscle quality, may be useful markers of throwing performance.